PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Purba, Saut; Silalahi, Donalson (UNIKA Santo Thomas, 2015)
Dividend policy is an interesting theme in financial research. The dividend policy often used to reduce conflicts of interest between shareholders and managers. Therefore, would be argued that the ownership structure affect the dividend policy. This study aims to: First, to explain the ownership structure and dividend policy. Second, to obtain the empirical evidence about the impact of ownership structure on dividend policy by used size, capital structure and profitability of the firm as control variables. The study was conducted in Indonesia Stock Exchange using the 198 companies as samples and use multiple regression as an analytical tool. Based on the results of the study suggested that: First, the institutional ownership before and after the control variables included positive and significant effect on the dividend payout ratio. Second, managerial ownership before and after the control variables included no significant effect on the dividend payout ratio. Third, the size of the company have significant positive effect on the dividend payout ratio. Fourth, capital structure and profitability of the firm has no significant effect on the dividend payout ratio.